Analysing the decline of the usage of the Lloyd's Open Form Agreement (LOF) for a vessel in distress at sea - Makubalo, Pumla (Department of Commercial Law, 2024)
The Lloyd's Open Form (LOF) standard form salvage contract emerged in the late 19th century and for about a century has, through its various revisions, been the most widely used international salvage contract worldwide. The latter part of the 20th century has seen a steady decline in its usage raising the question of whether there remains any role and place for it going into the future. A factor that has undoubtedly contributed to the decline in its usage is the enhanced safety of shipping during the course of the 20th century which has reduced the number of salvage opportunities. A further contributing factor to this decline has been the increasing number of instances of vessels being refused permission to seek refuge in coastal states' waters or harbours or being ordered out of those coastal waters, in either instance preventing any salvage of such vessels being successfully completed by bringing the vessel to safety, and the salvor from earning a salvage award. These instances have seen the increasing reliance on other forms of services contracts, such as towage contracts and wreck removal contracts, with fixed remuneration that is not earned on a no-cure, no-pay basis as is the case with LOF as with salvage contract generally, and this too has reduced the usage of LOF. These contracts also reduced the uncertainty with regard to the amount of the service providers remuneration that exists in the determination of salvage awards. The emergence of a range of standard form contracts in other parts of the world has provided competition for LOF within the international salvage contract marketplace, further contributing to the decline in its usage. Despite these developments, the LOF has survived through its ability to adapt to changing circumstances and maintain a place for itself, albeit reduced, going into the further, and its primary role and place in the marketplace going forward would seem to be in large-scale emergency salvage operations. The study also acknowledges the risks involved when salvors are entering perilous conditions where other mariners seek refuge, such as inclement weather or in waterways that other mariners are trained to avoid. Conditions such as the nature and size of the ship, its location, number of passengers, type of cargo, and political ramifications make each casualty operation unique and distinctive. It is acknowledged that the development of ship designs and the implementation of operating safety requirements has reduced prospects for salvage, which have been steadily declining, however the continuous usage of LOF is still important since it continues to be the salvage contract of choice in situations of time-sensitive emergencies at sea. Despite technological advancements, the LOF has evolved and responded to the new environment admirably. Additionally, the LOF has been able to allow for ongoing revisions as a result of difficulties brought on by international events, environmental issues, and arbitrator difficulties. Most significantly, it has demonstrated the ability to adapt to change as it occurs.